Endoscopic Ultrasound-Guided Celiac Plexus Neurolysis in Pancreatic Cancer: A Prospective Pilot Study of Safety Using 10 mL versus 20 mL Alcohol. (8th January 2013) - LeBlanc, Julia K.; Rawl, Susan; Juan, Michelle; Johnson, Cynthia; Kroenke, Kurt; McHenry, Lee; Sherman, Stuart; McGreevy, Kathy; Al-Haddad, Mohammad; DeWitt, John
Abstract : Background . The dose of alcohol used in EUS-CPN is not standardized. The objective was to compare the safety of 20 mL alcohol versus 10 mL alcohol during EUS-CPN for patients with pancreatic cancer-related pain. Methods . 20 patients were selected to receive 10 mL or 20 mL of alcohol during EUS-CPN. Followup was done at baseline, 24 hours, and weekly. Health-related quality of life (HRQoL) was assessed at baseline, week 2, week 4, and every 4 weeks thereafter until pain returned. Results . There were no major complications in both groups. Minor self-limited adverse effects were seen in 6 (30%) subjects and included lightheadedness in 1 (5%), transient diarrhea in 2 (10%), and transient nausea and vomiting in 3. Pain relief was similar in both groups: 80% in the 10 mL group and 100% in the 20 mL group (P = 0.21 ). The mean (± SD) duration of pain relief in the 10 mL and 20 mL groups was7.9 ± 10.8 and8.4 ± 9.2 weeks, respectively. 30% of patients in each group had complete pain relief. Conclusions . EUS-CPN using 20 mL of alcohol is safe. Similar clinical outcomes were seen in both groups. Further investigations to confirm these findings are warranted.